Anti-PD-1 Immunotherapy Combined With Stereotactic Body Radiation Therapy and GM-CSF as Salvage Therapy in a PD-L1-Negative Patient With Refractory Metastatic Esophageal Squamous Cell Carcinoma: A Case Report and Literature Review - Zhao, Xiangrong; Kong, Yuehong; Zhang, Liyuan (Frontiers in Oncology, 2020)
Keywords: immunotherapy1, radiotherapy2, PD-L13, esophageal squamous cell carcinoma4, GM-CSF5.Esophageal squamous cell carcinoma (ESCC) is a lethal malignancy with poor prognosis, which is often diagnosed at a late stage. Effective treatment options are limited when patients fail standard systemic therapy. The application of PD-1 inhibitors have led to a paradigm shift in the treatment of ESCC, but its efficacy as monotherapy is limited. Previous studies have shown that the antitumor effects may be reinforced when a PD-1 inhibitor is combined with radiotherapy or GM-CSF. This study aimed to report a case of a patient about ESCC negative expression of PD-L1, who experienced tumor progression after chemoradiotherapy and targeted therapy. However, a significant systemic effect was seen after PD-1 inhibitor combined with GM-CSF and stereotactic body radiotherapy (SBRT) for metastatic lesions. This study also reviewed several reports about combination therapy.